Tax and time : on the use and misuse of legal imagination - Infanti, Anthony C., 1968- (New York University Press, 2022)
How tax law perpetuates injustice but might instead be used as a powerful force for creating a more just and equitable society The relationship between tax law and society, Anthony C. Infanti asserts, is too often overlooked by those who work outside of the field of fiscal policy. Yet, the way a country collects and spends its revenue can be viewed as a quantifiable reflection of how a country sees itself, sending messages about both what it values now and what it aspires to be in the future.Tax and Time sheds light on two of the most misunderstood universal human experiences: time and taxes. Anthony C. Infanti asserts that time in tax law is the product of pure imagination and calls into question the world beyond time that we have created for ourselves. Written with clarity and powerful insight, Tax and Time demonstrates how the tax laws have been used to imaginatively manipulate time in ways that perpetuate economic and social injustice. With its social justice focus, the book brings a sorely needed critical perspective to technical tax policy discussions. Infanti calls for a systematic reexamination and reworking of the relationship between time and tax law, asserting that the power of the legal imagination to manipulate time in tax law can both correct past injustices and help us to envision--and actually work toward--a better and more just society.